Reading Paul with the reformers : reconciling old and new perspectives - Chester, Stephen J. (William B. Eerdmans Publishing Company, 2017)
In debates surrounding the New Perspective on Paul, the sixteenth-century Protestant Reformers are often characterized as the apostle's misinterpreters in chief. In this book Stephen Chester challenges that conception with a careful and nuanced reading of the Reformers' Pauline exegesis. Examining the overall contours of early Reformation exegesis of Paul, Chester contrasts the Reformers with their Roman opponents and explores particular contributions made by such key figures as Luther, Melanchthon, and Calvin. He relates their insights to contemporary debates in Pauline theology about justification, union with Christ, and other central themes, arguing that their work remains a significant resource today. Being published in the five-hundredth anniversary year of the Protestant Reformation, Reading Paul with the Reformers reclaims a robust, contemporary understanding of how the Reformers really read Paul